A link between plasma membrane calcium ATPase 2 (PMCA2), estrogen and estrogen receptor α signaling in mechanical pain. Issue 1 (December 2018) - Khariv, Veronika; Acioglu, Cigdem; Ni, Li; Ratnayake, Ayomi; Li, Lun; Tao, Yuan-Xiang; Heary, Robert; Elkabes, Stella
Abstract Earlier studies on genetically modified mice indicated that plasma membrane calcium ATPase 2 (PMCA2), a calcium extrusion pump, plays a novel and sex-dependent role in mechanical pain responses: female, but not male, PMCA2+/− mice manifest increased mechanical pain compared to female PMCA2+/+ mice. The goal of the present studies was to determine the contribution of ovarian steroids to the genotype- and sex-dependent manifestation of mechanical pain in PMCA2+/+ versus PMCA2+/− mice. Ovariectomy increased mechanical pain sensitivity and 17β-estradiol (E2) replacement restored it to basal levels in PMCA2+/+ mice, but not in PMCA2+/− littermates. Intrathecal administration of an estrogen receptor alpha (ERα) agonist induced ERα signaling in the dorsal horn (DH) of female PMCA2+/+ mice, but was ineffective in PMCA2+/− mice. In male PMCA2+/+ and PMCA2+/− mice, E2 treatment following orchidectomy did not recapitulate the genotype-dependent differential pain responses observed in females and the agonist did not elicit ERα signaling. These findings establish a novel, female-specific link between PMCA2, ERα and mechanical pain. It is postulated that PMCA2 is essential for adequate ERα signaling in the female DH and that impaired ERα signaling in the female PMCA2+/− mice hinders the analgesic effects of E2 leading to increased sensitivity to mechanical stimuli.